A porcine model of skin wound infected with a polybacterial biofilm. Issue 2 (7th February 2018) - Klein, Pavel; Sojka, Martin; Kucera, Jan; Matonohova, Jana; Pavlik, Vojtech; Nemec, Jan; Kubickova, Gabriela; Slavkovsky, Rastislav; Szuszkiewicz, Katarzyna; Danek, Petr; Rozkot, Miroslav; Velebny, Vladimir
Abstract: A clinically relevant porcine model of a biofilm-infected wound was established in 10 minipigs. The wounds of six experimental animals were infected with a modified polymicrobial Lubbock chronic wound biofilm consisting of Staphylococcus aureus, Enterococcus faecalis, Pseudomonas aeruginosa and Bacillus subtilis . Four animals served as uninfected controls. The wounds were monitored until they had healed for 24 days. The biofilm persisted in the wounds up to day 14 and significantly affected healing. The control to infected healed wound area ratios were: 45%/21%, 66%/37%, and 90%/57% on days 7, 10 and 14, respectively. The implanted biofilm prolonged inflammation, increased necrosis, delayed granulation and impaired development of the extracellular matrix as seen in histological and gene expression analyses. This model provides a therapeutic one-week window for testing of anti-biofilm treatments and for research on the pathogenesis of wound infections in pig that is clinically the most relevant animal wound healing model.